2015
DOI: 10.1063/1.4914128
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and bounds in thermal conductivity of planar Gaussian correlated microstructures

Abstract: In this study 2d two phase microstructures closely resembling the experimentally captured micrographs of the interpenetrating phase composites are generated using a Gaussian correlation function based method. The scale dependent bounds on the effective thermal conductivity of such microstructures are then studied using Hill-Mandel boundary conditions. A scaling function is formulated to describe the transition from statistical volume element (SVE) to representative volume element (RVE), as a function of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…One extreme case δ = 1 signifies the description at the level of one grain, while the second extreme δ → ∞ is the RVE limit, and, in general, one wants to know with what precision is the RVE attained at any finite δ for specific physical and geometric parameters. Numerically generated micrograph of Gaussian correlated microstructure [33].…”
Section: (A) Random Microstructurementioning
confidence: 99%
See 3 more Smart Citations
“…One extreme case δ = 1 signifies the description at the level of one grain, while the second extreme δ → ∞ is the RVE limit, and, in general, one wants to know with what precision is the RVE attained at any finite δ for specific physical and geometric parameters. Numerically generated micrograph of Gaussian correlated microstructure [33].…”
Section: (A) Random Microstructurementioning
confidence: 99%
“…To better resolve the stress and strain distributions at the interface of two phases, quadratic elements are used instead of bilinear elements; the mesh density becomes more important in ensuring the accuracy of the solution obtained using FEM in the case of strong mismatch in the phases' properties [33]. For our microstructure of a random chessboard at volume fraction 0.5, a comprehensive mesh sensitivity analysis was conducted in Zhang & Ostoja-Starzewski [9], where it was found that, for the chosen constituent properties, the mesh density of 4 × 4 elements per one square of the chessboard provides a stable solution and sufficient accuracy.…”
Section: (C) Scaling Functionmentioning
confidence: 99%
See 2 more Smart Citations